2018
DOI: 10.1002/lio2.159
|View full text |Cite
|
Sign up to set email alerts
|

99mTc‐HMPAO‐leukocyte scintigraphy for diagnosis and therapy monitoring of skull base osteomyelitis

Abstract: ObjectiveSkull base osteomyelitis (SBO) is a rare but life‐threatening disease observed in elderly diabetic patients, with high risk of recurrence and difficult therapeutic management. The diagnosis is ascertained from a set of clinical, biological, and imaging findings. CT and MRI allow initial diagnosis, but are not accurate to affirm healing at the end of therapy. 99mTc‐HMPAO‐Leucocyte Scintigraphy (LS) is highly sensitive and specific for the detection of infection. The aim of this study was to evaluate LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…MRI or CT as single modality is insufficient to be crucial in diagnosing malignant otitis externa [24]. Technetium 99m scans may show osteoblastic activity that may be useful for therapeutic monitoring of SBO [25]. Hybrid technique PET–MRI or CT-MRI present complementary value that strengthens imaging modalities [24, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI or CT as single modality is insufficient to be crucial in diagnosing malignant otitis externa [24]. Technetium 99m scans may show osteoblastic activity that may be useful for therapeutic monitoring of SBO [25]. Hybrid technique PET–MRI or CT-MRI present complementary value that strengthens imaging modalities [24, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid technique PET–MRI or CT-MRI present complementary value that strengthens imaging modalities [24, 26]. However, soft-tissue abnormalities in MRI over the mastoid area and/or in infratemporal fossa, or CT scan demonstrating the presence of bony destruction in mastoid area, and clinical manifestations of otitis allow initial diagnosis of malignant otitis externa [4, 8, 15, 21, 22, 24, 25]. In our study, CT scans revealed inflammatory process in the tympanic cavity with features of bony destruction of the mastoid process in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation between both entities is crucial because they involve different treatment methods and planning. 1215 The treatment of osteitis involves antibiotics alone, whereas osteomyelitis must be treated surgically with debridement and sequestrectomy. 27…”
Section: Discussionmentioning
confidence: 99%
“…1012 Routine magnetic resonance imaging (MRI) and isotope studies are used for the prediction of skull base osteomyelitis, but their results are non-specific. 1315 Diffusion-weighted imaging offers better characterisation of the soft tissues and their physiological processes because it reflects the random motion of the water protons, which is disturbed by the intracellular organelles and macromolecules located within the tissues. 16,17 Diffusion-weighted imaging is commonly used for the assessment of head and neck cancer, 17,18 soft tissue infection, 19,20 and bone infection with osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…A tagged white blood cell study can be used for confirming healing at the end of antibiotic therapy. 1,11,36 Overall, the literature has variable data regarding the overall diagnostic value of nuclear medicine studies. 37 A recent review of malignant otitis externa literature revealed pooled sensitivities for technetium-99 and gallium-67 of 85.1% and 71.2%, respectively, with poor specificity; however, the data were deemed insufficient for a meta-analysis.…”
Section: Pathologymentioning
confidence: 99%